Effect of mineral fertilisation on tuber yield and quality in yams (Dioscorea alata and Dioscorea rotundata) - Afolabi, F.; Matsumoto, R.; Akinwande, B.; Otegbayo, B.; Asfaw, A. (MDPI, 2023)
This study assessed mineral fertilisation impact on tuber yield and food quality in yam genotypes—Dioscorea alata and Dioscorea rotundata. Four genotypes, each from D. alata and D. rotundata, were used in field experiments conducted in Ibadan, Nigeria, during the 2017 and 2018 cropping seasons. Experiments were conducted under low soil NPK fertility conditions with and without Fertiliser treatments. Plots subjected to fertiliser treatment received recommended NPK rate for the area. Tuber yield, functional and pasting properties of yam flour, and sensory attributes of pounded yams were collected. The results revealed varying responses of the genotypes to tuber yield and food quality following fertiliser application. Fertiliser application has generally increased fresh tuber yield. However, it had an impact on the flour quality and textural attributes of pounded yams for some genotypes. In genotypes Danacha and TDa0200012, Fertiliser application increased fresh tuber weight by 29.6% and 28.3%, and dry tuber weight by 19.7% and 24.9%, respectively, without compromising tuber quality. This implies that both genotypes exhibited a greater capacity for nutrient uptake and nutrient use efficiency. However, for genotype Ojuiyawo, Fertiliser application effectively increased tuber yield but negatively affected tuber quality. Our results emphasize the importance of assessing the impact of fertilization on tuber yield and quality for each genotype and selecting the appropriate genotype to improve productivity through mineral fertilization. The outcomes of this study have broader applicability in improving yam productivity across sub-Saharan Africa and are useful for sustainable agriculture in yam-growing regions.